WOMEN'S EMANCIPATION IN THE PERSPECTIVE OF THE QUR'AN: A THEMATIC QUR'AN STUDY ON MORAL AND SOCIAL EQUALITY WITH A GROUNDED THEORY APPROACH - Maulidya Rahmani; Muhammad Alif (Adisam Publisher, 2026)
This study aims to analyze the idea of women's emancipation from the perspective of the Qur'an using the thematic approach of the Qur'an and the analysis of Grounded Theory. The background of this research is the emergence of various discussions about the position and role of women in society which are often understood in a limited way without considering the broader understanding of the Qur'an. The approach used in this study is qualitative with a normative-theological approach. The data used came from verses of the Qur'an that were relevant to women's themes, especially those that described the origin of human creation, moral and spiritual responsibilities, and social and economic rights that women have. Data collection is carried out through the identification and classification of related verses, then analyzed using the thematic method of the Qur'an. Data analysis was carried out with a Grounded Theory approach through the stages of open coding, axial coding, and selective coding to find the main concepts contained in the text of the verse. The results of the study show that the idea of women's emancipation in the Qur'an can be understood through three main dimensions, namely ontological equality, moral equality, and social equality. Ontological equality asserts that men and women come from a similar source of creation. Moral equality shows that both have an equal spiritual responsibility and opportunity to reap the rewards of good deeds. On the other hand, social equality can be seen from the Qur'an's recognition of economic rights, legal protection, and women's participation in society. These findings show that the Qur'an provides a strong normative basis for respecting women's dignity as well as acknowledging their role in human life.